Assessment of ovarian reserve after cystectomy versus 'one-step' laser vaporization in the treatment of ovarian endometrioma: a small randomized clinical trial. Issue 12 (9th October 2018) - Candiani, M; Ottolina, J; Posadzka, E; Ferrari, S; Castellano, L M; Tandoi, I; Pagliardini, L; Nocuń, A; Jach, R
Abstract: STUDY QUESTION: Does CO2 laser vaporization offer better results in treating endometrioma in terms of ovarian reserve preservation compared to traditional cystectomy? SUMMARY ANSWER: Assessing both antral follicle count (AFC) and serum anti-Müllerian hormone (AMH) levels as measures of ovarian reserve, the results suggest that CO2 technology may be an alternative treatment for endometrioma, causing minimal damage to adjacent healthy ovarian tissue. WHAT IS KNOWN ALREADY: Excisional surgery has been questioned as an ideal surgical approach for endometriomas because it is associated with potential reduction of ovarian reserve. Recently, vaporization with CO2 laser in-line-of-sight, according to the 'three-step procedure', has been proposed as the best method to preserve ovarian function. However, no randomized controlled trials have been conducted to compare cystectomy and 'one-step' CO2 fiber laser vaporization (without GnRH agonist therapy) with respect to the ovarian reserve. STUDY DESIGN, SIZE, DURATION: A multicentre randomized clinical trial including 60 patients was performed between July 2017 and February 2018. Computerized randomization was conducted to allocate them in a proportion of 1:1 either to Group 1 (laparoscopic stripping: cystectomy) or Group 2 (CO2 laser vaporization). Patients in Group 1 underwent a standardized laparoscopic stripping technique; patients in Group 2 underwent drainage of the cyst content, biopsy and vaporization of the internal wall with a CO2 fiber laser. Patients underwent pelvic ultrasound examination to determine the AFC and blood sampling to determine AMH levels before surgery and at 1- and 3-month follow-up. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients undergoing surgery for symptomatic endometriomas (infertility and/or pelvic pain) larger than 3 cm were randomized in two groups according to the surgical technique. Patients aged ≥40 years, or with deep infiltrating endometriosis/adenomyosis, or previously submitted to surgical procedures on the ovaries or to hysterectomy were excluded from the study. The primary endpoint was the comparison of intra-group AFC changes before and after surgery (ΔAFC) between the two groups (ΔAFC Group 1 versus ΔAFC Group 2). The secondary endpoint was the modification of serum AMH before and after surgery (ΔAMH) between the two groups (ΔAMH Group 1 versus ΔAMH Group 2). MAIN RESULTS AND THE ROLE OF CHANCE: The AFC of the operated ovary was significantly increased in Group 2 (laser vaporization) compared with Group 1 (cystectomy) after surgery (Group 1: from 4.1 ± 2.2 [mean ± SD] at baseline to 6.3 ± 3.5 at 3-month follow-up; 95% CI: 0.9–4; Group 2: from 3.6 ± 1.9 at baseline to 8.6 ± 4.2 at 3-month follow-up; 95% CI: 2.8–7.1; P = 0.016); serum AMH levels were significantly reduced at 3 months in Group 1 (from 2.6 ± 1.4 ng/mL at baseline to 1.8 ± 0.8 ng/mL at 3-month follow-up; 95% CI: −1.3 to −0.2; P = 0.012) compared with no reduction in Group 2 (from 2.3 ± 1.1 ng/mL at baseline to 1.9 ± 0.9 ng/mL at 3-month follow-up; 95% CI: −1 to −0.2; P = 0.09). LIMITATIONS, REASON FOR CAUTION: The key limitations of the trial were the low accuracy of AFC in estimating the ovarian reserve in ovaries with endometriomas, the limited study size and the relatively short follow-up, which do not allow us to draw definitive conclusions. WIDER IMPLICATIONS OF THE FINDINGS: The present study suggests that CO2 technology may treat endometrioma with minimal damage to the adjacent healthy ovarian tissue; however, this study should be considered as a preliminary clinical trial, intended to stimulate future larger trials to address this clinically relevant issue. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov NCT03227640. TRIAL REGISTRATION DATE: 9 July 2017. DATE OF FIRST PATIENT'S ENROLLMENT: 24 July 2017.